Validity of Interactive Instructional Media Based on CMS-WordPress Website on Hydrocarbon Topic For Senior High School Learning - Monica Putri Safira; Effendi Effendi (Universitas Negeri Padang, 2022)
Hydrocarbon is a topic that is considered difficult by students, the lack of concept understanding leads the students into misconceptions. Curriculum 2013 demands the students to actively seek, proceed, and developing knowledge in the learning process, as well as skillfully in using media and technology. This study aims to produce interactive learning media based on the CMS-WordPress website on hydrocarbon materials and determine the level of its validity. The type of research used is design research using the Plomp model. The research procedure includes the preliminary research stage, the prototyping stage, and the assessment phase. This research is limited to the prototyping stage, namely the validity test to produce prototype III. The media that developed as a whole is categorized as valid, based on the Aiken’s V formula analysis, with a content validity value: 0.86; construct validity value: 0.87; and media validity: 0.94.